Urban Parks on the Political Agenda of the Municipality of Sao Paulo-SP - Régis, Milena de Moura; Côrtes, Pedro Luiz; Nascimento, Ana Paula Branco do (Periódico Eletrônico Fórum Ambiental da Alta Paulista, 2023)
Urban parks perform different and important functions in cities, providing numerous environmental benefits and improving the quality of life of the city population. Studies that address the value of urban parks, as well as discuss the relevance of municipal planning and public policies aimed at building environmentally healthy cities, are essential. These aspects justify the development of this study, which aimed to identify whether urban parks are part of the political agenda of the previous and current management of the Municipality of São Paulo/SP. For the development of the theoretical framework of this study, a systematic review was carried out in the ProQuest, Scielo, Scopus databases, in which articles published between 2010 and 2020 were sought. In order to identify whether urban parks are part of the political agenda of the previous and current management of the Municipality of São Paulo/SP, a documentary research was carried out, and for that the Government Plan and the Guidelines of the Government Plan of the current/re-elected management from the city of São Paulo were consulted. The data revealed the importance of urban parks for the maintenance of environmental quality in urban areas and for the quality of life of the population that resides and transits through cities. Furthermore, it showed that urban parks are part of the political agenda of the previous and current/re-elected management of the municipality of São Paulo. Thus, urban parks are among the themes to which municipal management has dedicated its attention and has been developing a set of alternative actions for the maintenance of parks.